KONDISI SOSIAL EKONOMI MASYARAKAT PADA MASA PANDEMI COVID-19 DI DESA SEA MITRA KECAMATAN PINELENG KABUPATEN MINAHASA (Socio Economic Conditions of The Community During the Covid-19 Pandemic in Sea Mitra Village, Pieneleng Sub District, Minahasa Regency) - Yohan Kristian David Kansil; Theodora M. Katiandagho; Jenny Baroleh (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
During the Covid-19 pandemic, the impact of the pandemic on the economy has made it difficult for the people of the Sea Mitra Village to find jobs which include casual (informal) workers, As a result the wages or salaries received are not suitable for the daily needs of the family. In the social sector, it affects community groups resulting in worship meetings and community organizations not being able to be held in crowded places. The objective of this research is to determine and describe the socio economic conditions of the community during the Covid-19 pandemic in Sea Mitra Village Pineleng Sub District Minahasa Regency. This research was conducted from May 2021 July 2021. The data collected is primary data obtained from direct interviews with the community using a questionnaire. Secondary data were obtained from the Sea Mitra Village Office, as well as data related to research taken from the internet. Sampling wa carried out by means of Simple Random Sampling, namely as many as 28 samples. The research result showed that the socio-economic conditions of the Sea Mitra Village comunity during the Covid-19 pandemic experienced a decrease in main income and side income before the pandemic and during the pandemic.